Pengaruh Kegiatan Kokurikuler Bangunlah Jiwa dan Raganya Terhadap Pembentukan Karakter Tanggung Jawab Siswa SMP Negeri 18 Bandar Lampung - Muhammad Bagaskara; Berchah Pitoewas; Abdul Halim; Devi Sutrisno Putri; Nurhayati . (Jurnal Pendidikan Sosial Dan Konseling, 2026)
This study aims to analyze the influence of co-curricular activitiesAwaken the Soul and Bodytowards the formation of responsible character of students at SMP Negeri 18 Bandar Lampung. This study uses the methodafter the factUsing a quantitative approach, the research subjects were students of SMP Negeri 18 Bandar Lampung. The data analysis technique used was simple linear regression. The results of the study showed that co-curricular activitiesAwaken the Soul and Bodyhas a significant influence on the formation of students' responsible character. This influence is reflected in the implementation of various activities, such as the healthy lliving campaign, Satria Baik, anti-bullying and violence outreach, andself-assessment, which encourages students to take responsibility for their own choices and reactions, focus on internal change, act based on personal values and commitments, be independent of external goals, and avoid blaming, complaining, and making excuses. The most prominent indicator of responsibility is seen in students' ability to act based on personal values and commitments and be independent of external goals, while the Satria Baik indicator shows relatively lower achievement. These findings confirm that co-curricular activities not only play a role in shaping students' personal responsibility, but also strengthen attitudes of mutual respect and social responsibility within the school environment.